A Balanced Scorecard Analysis to Evaluate Consumer, Employee Satisfaction, and Internal Business Processes in Blood Transfusion Units in dr. Kariadi Hospital - Tri Wardhani, Ria; Jati, Sutopo Patria; Kartasurya, Martha Irene (Management Analysis Journal, 2022)
The hospital is a service organization for patients (consumers). Service is expected to provide comprehensive consumer desires. Previous research has not much elaborated on the balanced scorecard and analysis of the constituent factors of customer and employee satisfaction. This study aims to analyze the balanced scorecard, the constituent factors of customer and employee satisfaction in dr. Kariadi Hospital. The number samples used as many as 72 consumer respondents who use hospital services and 27 hospital employees. The research method uses a balanced scorecard and analysis of the constituent factors of customer and employee satisfaction. The analysis results show that the human resource factor still requires improvement compared to the customer factor. This study confirms that efforts to provide optimal service have been made to satisfy customers. But on the other hand, efforts to provide satisfaction to employees are still lacking; therefore, efforts are needed to provide satisfaction.